2020
DOI: 10.1080/15592324.2019.1710935
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated TOR signaling lengthens circadian period in Arabidopsis

Abstract: By timing many diel rhythmic events, circadian clock provides an adaptive advantage for higher plants. Meanwhile, circadian clock displays plasticity and can be entrained by the external environmental cues and internal factors. However, whether cellular energy status can regulate circadian clock is largely unknown in higher plants. The evolutionarily conserved TOR (target of rapamycin) signaling among eukaryotic organisms has been implicated as an integrator for cellular nutrient and energy status. Here, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Evidence for these more direct effects of TOR on clocks comes from studies on Drosophila ( Zheng and Sehgal, 2010 ), human cell lines ( Feeney et al, 2016 ; Walton et al, 2018 ), and both SCN and peripheral tissues of mice ( Cao, 2018 ; Lipton et al, 2017 ). In recent studies on Arabidopsis , TOR was found to be essential for glucose- and nicotinamide-mediated control of the circadian period ( Zhang et al, 2019 ), and knocking down TOR activity with inhibtors, micro-RNA or RNAi was found to lengthen the circadian period ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for these more direct effects of TOR on clocks comes from studies on Drosophila ( Zheng and Sehgal, 2010 ), human cell lines ( Feeney et al, 2016 ; Walton et al, 2018 ), and both SCN and peripheral tissues of mice ( Cao, 2018 ; Lipton et al, 2017 ). In recent studies on Arabidopsis , TOR was found to be essential for glucose- and nicotinamide-mediated control of the circadian period ( Zhang et al, 2019 ), and knocking down TOR activity with inhibtors, micro-RNA or RNAi was found to lengthen the circadian period ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, studies have revealed that mTORC1 signaling is involving in photic entrainment of the suprachiasmatic nuclei (SCN) circadian clock, thereby linking the metabolic states to circadian clock regulation (Cao et al, 2010, 2013; Cao and Obrietan, 2010; Cao, 2018; Liu et al, 2018; Ramanathan et al, 2018). Recent studies have also shed light on the involvement of glucose–TORC1 signaling in plant circadian clock regulation (Li et al, 2019; Zhang et al, 2019; Wang et al, 2020). Vitamin B 3 (nicotinamide, NAM), a key precursor/byproduct for NAD + biosynthesis, can affect the cytosolic ATP concentration, blocking the effect of glucose–TOR energy signaling on period length adjustment, root meristem activation, and primary root growth (Zhang et al, 2019; Wang et al, 2020).…”
Section: Plant Tor Signaling: Upstream Signals and Regulatorsmentioning
confidence: 99%
“…Recent studies have also shed light on the involvement of glucose–TORC1 signaling in plant circadian clock regulation (Li et al, 2019; Zhang et al, 2019; Wang et al, 2020). Vitamin B 3 (nicotinamide, NAM), a key precursor/byproduct for NAD + biosynthesis, can affect the cytosolic ATP concentration, blocking the effect of glucose–TOR energy signaling on period length adjustment, root meristem activation, and primary root growth (Zhang et al, 2019; Wang et al, 2020). Interestingly, the circadian core oscillators, PRR5/7/9 (pseudo response regulators 5/7/9) (Harmer, 2009) also promotes TOR mRNA stability through direct inhibitions of the expression of TZF1 (tandem zinc finger 1, a processing body localized RNA‐binding protein) (Qu et al, 2014), which could directly bind to TOR mRNA and decrease its stability (Li et al, 2019).…”
Section: Plant Tor Signaling: Upstream Signals and Regulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy‐related genes ( ATGs ) were first discovered in yeast, and more than 40 ATGs have been characterized by different groups in the past few decades (Tsukada and Ohsumi, 1993; Masclaux‐Daubresse et al, 2017; Qi et al, 2021). TARGET OF RAPAMYCIN ( TOR ), a core metabolic regulator gene, is also a key regulator of autophagy that participates in regulation of the circadian clock (Zhang et al, 2019; Wang et al, 2020b). In plants, the TOR kinase signaling pathway regulates autophagy by phosphorylating the ATG1 and ATG13 proteins to inhibit autophagy initiation when nutrients are abundant.…”
Section: Introductionmentioning
confidence: 99%